5(x-5)+93=9x-4(x-7)

Simple and best practice solution for 5(x-5)+93=9x-4(x-7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-5)+93=9x-4(x-7) equation:



5(x-5)+93=9x-4(x-7)
We move all terms to the left:
5(x-5)+93-(9x-4(x-7))=0
We multiply parentheses
5x-(9x-4(x-7))-25+93=0
We calculate terms in parentheses: -(9x-4(x-7)), so:
9x-4(x-7)
We multiply parentheses
9x-4x+28
We add all the numbers together, and all the variables
5x+28
Back to the equation:
-(5x+28)
We add all the numbers together, and all the variables
5x-(5x+28)+68=0
We get rid of parentheses
5x-5x-28+68=0
We add all the numbers together, and all the variables
40!=0
There is no solution for this equation

You can always share this solution

See similar equations:

| 6n-6=3n-6 | | 6(4x-8)-5x+6=15 | | c6+7=9 | | 3-5(2x+4)=6x+1 | | H+5=-18h-19+17h | | -14-20+16s=16-9s | | 5x+4=9x5 | | -15.94+20t=16.7t+18.2t | | -5+15g=12g+19+g | | 60+90+(4x-20)=180 | | -18k+16-19=-16-19k | | -x+6x=-9 | | 5x+12=3+6x | | -1.7s-19.98=13.9s+20+11.5 | | 5x-45+4x=3-10x+9 | | 36?9u=??27 | | 5d+9=9 | | Y=-(x-1)^2+25 | | x^2+18=8 | | -w+9=-7+8w-8w | | -1.32=3(1.5y-0.5) | | 8b=23-111 | | -17+4c=11c+5-5c | | 8b=56b= | | -5-6h=7 | | 13+20f=4f-17+18f | | 15x+5=80+6x6 | | 13+15q+8=20q-19 | | 5m-15=2m-9 | | 16/(x-3)=10/x | | -16-8t+5t=t+20 | | r-7/6=5 |

Equations solver categories